2013
DOI: 10.1002/eji.201243026
|View full text |Cite
|
Sign up to set email alerts
|

IL‐15 modulates the balance between Bcl‐2 and Bim via a Jak3/1‐PI3KAkt‐ERK pathway to promote CD8αα+ intestinal intraepithelial lymphocyte survival

Abstract: IL-15 is an essential survival factor for CD8αα+ intestinal intraepithelial lymphocytes + iIEL survival by both increasing Bcl-2 levels and dissociating Bim from Bcl-2 through activation of a Jak3-Jak1-PI3K-Akt-ERK1/2 pathway, which differs from a previously reported IL-15-induced survival signal.Keywords: Bcl-2 r Bim r CD8αα + intestinal intraepithelial lymphocytes (iIELs) r IL-15Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionIntest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 45 publications
0
32
2
Order By: Relevance
“…NKT1 cells are the predominant subset in C57BL/6 mice Lee et al, 2013), although in several other inbred mouse strains NKT2 and NKT17 cells are for more frequent. NKT2 cells in the thymus constitutively produce IL-4, which causes the differentiation of a population of Eomesodermin (Eomes)-expressing innate-like CD8 + T lymphocytes with a memory or antigen-experienced phenotype (Lai et al, 2013;Weinreich, Odumade, Jameson, & Hogquist, 2010).…”
Section: Effector Functionsmentioning
confidence: 99%
“…NKT1 cells are the predominant subset in C57BL/6 mice Lee et al, 2013), although in several other inbred mouse strains NKT2 and NKT17 cells are for more frequent. NKT2 cells in the thymus constitutively produce IL-4, which causes the differentiation of a population of Eomesodermin (Eomes)-expressing innate-like CD8 + T lymphocytes with a memory or antigen-experienced phenotype (Lai et al, 2013;Weinreich, Odumade, Jameson, & Hogquist, 2010).…”
Section: Effector Functionsmentioning
confidence: 99%
“…A recent study found a converse regulation of Bcl-2-family proteins by either IL-7 or TCR signals, where IL-7, for instance, upregulated Bcl-2 mRNA but this upregulation was dominantly inhibited by concurrent CD3 stimulation [6]. In intestinal intraepithelial CD8αα + T cells, IL-15 was also found to upregulate Mcl-1 and Bcl-2 [15].…”
Section: Introductionmentioning
confidence: 95%
“…Ligand binding stimulates the activation of the tyrosine kinase JAK3 associated with the intracellular region of IL-2Rgc, which activates a number of downstream intracellular pathways, including those involving STAT5, PI3K, and ERK, the latter lying downstream of MEK (11,12). Inactivating mutations in human IL-2Rgc cause T 2 B + SCID, characterized by decreased numbers of T cells and a diminished immune response (13).…”
mentioning
confidence: 99%